2022
DOI: 10.1515/culture-2022-0156
|View full text |Cite
|
Sign up to set email alerts
|

Fansubbers’ Subtitling Strategies of Swear Words from English into Arabic in the Bad Boys Movies

Abstract: This research investigates the strategies used by fansubbers to translate English culture-bound expressions into Arabic. It further investigates the functions of swear words and how the fansubber regenerated their functional connotations. The corpus of the study consists of English subtitles and Arabic fansubs of the Bad Boys movies. The researchers analyzed the data both quantitatively and qualitatively. The frameworks adopted in this research are the strategies proposed by Diaz-Cintas and Remael and the clas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Their facial expressions have clearly shown their disagreement with the discourse of some fundamentalists who accuse others of blasphemy or adopt a discourse that fuels hatred, intolerance, and hostility. While this finding of the study may not have been reported in other studies, the use of deletion and accommodation strategies to meet some sociocultural norms has been reported in studies including [57][58][59]. The analysis of these cognitive processes can shed more light on the choices of translators.…”
Section: Discussionmentioning
confidence: 60%
“…Their facial expressions have clearly shown their disagreement with the discourse of some fundamentalists who accuse others of blasphemy or adopt a discourse that fuels hatred, intolerance, and hostility. While this finding of the study may not have been reported in other studies, the use of deletion and accommodation strategies to meet some sociocultural norms has been reported in studies including [57][58][59]. The analysis of these cognitive processes can shed more light on the choices of translators.…”
Section: Discussionmentioning
confidence: 60%
“…However, it diverges from other research, such as Balfaqeeh’s (2009) determination that Arab students tend to favor the domestication strategy in translation, and Alsharhan’s (2020) observation that euphemism and omission strategies are commonly used for translating taboo expressions. Debbas and Haider (2020) similarly discovered that euphemistic expressions and word omission dominate as strategies for translating taboos, whereas Al-Zgoul and Al-Salman (2022) highlighted omission as the predominant strategy in translating swear words, followed by transposition, explicitation, calques, loanwords, lexical invention, and compensation.…”
Section: Discussionmentioning
confidence: 99%
“…Debbas and Haider (2020) highlighted techniques like scene deletion and word omission in subtitles for Family Guy. Al-Zgoul and Al-Salman (2022) studied Arabic expletive translation, with omission being the most common strategy. Rouabhia et al .…”
Section: Review Of the Literaturementioning
confidence: 99%
“…); and b) defecation, micturition and organs and acts of sex, to mention a few. Due to the extensive spread of this phenomenon, innumerable studies have been conducted, particularly in relation to subtitling movies, and to a lesser extent, tv series (Al-Yasin and Rabab'ah 2019;Al-Zgoul and Al-Salman 2022;Haider and Hussein 2022).…”
Section: 1mentioning
confidence: 99%